Vacancies and holes in bulk and at 180° domain walls in lead titanate. (13th November 2017) - Paillard, Charles; Geneste, Grégory; Bellaiche, Laurent; Dkhil, Brahim
Abstract: Domain walls (DWs) in ferroic materials exhibit a plethora of unexpected properties that are different from the adjacent ferroic domains. Still, the intrinsic/extrinsic origin of these properties remains an open question. Here, density functional theory calculations are used to investigate the interaction between vacancies and 180° DWs in the prototypical ferroelectric PbTiO3, with a special emphasis on cationic vacancies and released holes. All vacancies are more easily formed within the DW than in the domains. This is interpreted, using a phenomenological model, as the partial compensation of an extra-tensile stress when the defect is created inside the DW. Oxygen vacancies are found to be always fully ionized, independently of the thermodynamic conditions, while cationic vacancies can be either neutral or partially ionized (oxygen-rich conditions), or fully ionized (oxygen-poor conditions). Therefore, in oxidizing conditions, holes are induced by neutral and partially ionized Pb vacancies. In the bulk PbTiO3, these holes are more stable as delocalized rather than small polarons, but at DWs, the two forms are found to be possible.